Perceived healthiness of sugary drinks and related social norms among adults in five countries: evidence from the International Food Policy Study - Virginie Drolet-Labelle; Christine M. White; Jean Adams; Sharon I. Kirkpatrick; Alejandra Jáuregui; Lilia S. Pedraza; Véronique Provencher; Gary Sacks; James F. Thrasher; Gabriela C. Armendariz; Simón Barquera; David Hammond; et al. (Nutrition Journal)
Abstract Background A better understanding of correlates of sugary drink consumption is essential to inform public health interventions. This study examined differences in perceived healthiness of sugary drinks and related social norms between countries, over time, and sociodemographic groups and associations with sugary drink intake. Methods This study used annual cross-sectional data from the International Food Policy Study from 2018 to 2021 in Australia, Canada, the United Kingdom, the United States, and Mexico. Analyses examined perceived healthiness of eight beverage types and two types of perceived social norms (descriptive, injunctive) that discourage sugary drink consumption. The 24-item Beverage Frequency Questionnaire was used to estimate beverage intake in the past 7 days. Logistic regression models examined trends over time in odds of perceiving each beverage type as unhealthy and agreeing with social norms discouraging sugary drink consumption, across countries and sociodemographic characteristics. Negative binomial regressions examined associations between perceived healthiness, social norms and consumption. Results Energy drinks, regular soft drinks, and diet soft drinks were most frequently perceived as unhealthy in all countries, while water and 100% juice were least frequently perceived as unhealthy. Participants in Mexico had higher odds of perceiving 100% juice, chocolate milk, and iced tea as unhealthy in 2021 compared to 2018 (AOR = 1.71 99%CI 1.10–2.64; AOR = 2.69, 99%CI 1.70–4.26; AOR = 1.79, 99%CI 1.15–2.76; respectively), with little change in other countries. Agreement with social norms discouraging consumption of sugary drinks was higher in Mexico than in other countries. Trends in social norms over time were mostly stable, except in Mexico where participants had higher odds of agreeing with both norms in 2020 compared to 2018 (AOR = 1.27, 99%CI 1.09–1.48 for a descriptive norm and AOR = 1.27 99%CI 1.09–1.49 for an injunctive norm). In most countries, perceiving a beverage as unhealthy and agreeing with social norms discouraging consumption of sugary drink were associated with lower sugary drink consumption, with varying strength of associations across countries and beverage types. Conclusions Shifts over time in social norms and perceived healthiness observed in Mexico and associations with intake of sugary drinks in most countries suggest that targeted interventions to change norms and perceptions could help reduce sugary drink consumption.